The Impact of Brain Based Learning Strategy on Mathematical Communication Ability of Grade V Elementary School Students - Amelia, Winda; Sundi, Venni Herli; Supena, Asep; Yufiarti, Yufiarti (International Journal of Elementary Education, 2022)
Most students think of mathematics as a complicated and burdensome subject, so there tends to be a lack of interest in studying mathematics. Mathematical communication skills become one of the important things in learning. Therefore, so that math learning like, need made an effort to adopt learning strategies that can improve. Mathematical communication skills of elementary school students. This study aims to determine the differences in which learning strategies result in higher mathematical communication skills between students and students Brain Based Learning with conventional learning strategies. This research is a type of quasi-experimental research (quasi-experimental). Sampling with cluster random sampling technique. The data analysis technique used normality, homogeneity, hypothesis testing and statistical hypotheses. The conclusions of this study are as follows: 1). An increase in the average value of 58.15 experienced by the experimental class with Brain Based Learning strategy higher than the average value of the control class of 14.9. So that the mathematical communication skills of students in the experimental class in mathematics experienced a significant increase compared to the control group; 2). The results of statistical calculations obtained t count is 8.25 and the value of t table is 1.99 which is smaller than the value of t count, so Brain Based Learning strategy has a positive impact on the mathematical communication skills of class V in mathematics learning.